Surfactants as mesogenic agents in layer-by-layer assembled polyelectrolyte/surfactant multilayers: Nanoarchitectured "soft" thin films displaying a tailored mesostructure - Piccinini, Esteban (2018)
Interfacial supramolecular architectures displaying mesoscale organized components are of fundamental importance for developing materials with novel or optimized properties. Nevertheless, engineering the multilayer assembly of different building blocks onto a surface and exerting control over the internal mesostructure of the resulting film is still a challenging task in materials science. In the present work we demonstrate that the integration of surfactants (as mesogenic agents) into layer-by-layer (LbL) assembled polyelectrolyte multilayers offers a straightforward approach to control the internal film organization at the mesoscale level. The mesostructure of films constituted of hexadecyltrimethylammonium bromide, CTAB, and polyacrylic acid, PAA (of different molecular weights), was characterized as a function of the number of assembled layers. Structural characterization of the multilayered films by grazing-incidence small-angle X-ray scattering (GISAXS), showed the formation of mesostructured composite polyelectrolyte assemblies. Interestingly, the (PAA/CTA)n assemblies prepared with low PAA molecular weight presented different mesostructural regimes which were dependent on the number of assembled layers: a lamellar mesophase for the first bilayers, and a hexagonal circular mesophase for n ≥ 7. This interesting observation was explained in terms of the strong interaction between the substrate and the first layers leading to a particular mesophase. As the film increases its thickness, the prevalence of this strong interaction decreases and the supramolecular architecture exhibits a "bulk" mesophase. Finally, we demonstrated that the molecular weight of the polyelectrolyte has a considerable impact on the meso-organization for the (PAA/CTA)n assemblies. We consider that these studies open a path to new rational methodologies to construct "nanoarchitectured" polyelectrolyte multilayers.